Effect of an energy supplementation, weaning and oestrous synchronisation on ovarian activity and ovulation in early postpartum primiparous Bos indicus cows raised in the tropics of Costa Rica - Estrada, Sandra (2015)
To evaluate the effect of an energy supplementation, 26 postpartum Bos indicus cows were assigned either to receive an energy diet supplementation (n ≤ 11, SSD) or no supplementation (n ≤ 15, NSSD). Cows in the SSD treatment received a diet consisting of 5.5% crude protein, 2.85 Mcal digestible energy per head per day, at 1% ratio of the average bodyweight, started 23.5 ± 3.4 days after calving and continued for 44 days. In contrast, NSSD cows were grazing only native pastures during the experiment. All cows were synchronised at 65 days postpartum with a subcutaneous progestin ear implant (Norgestomet) for 9 days and an injection of oestradiol valerate and Norgestomet at the same time as implant placement. A random sample of six animals from each treatment was scanned with ultrasound every 6 h and the dominant follicle (s) was measured until ovulation occurred or after 114 h. The nadir of body condition score for the NSSD was observed at 37.5 ± 3.4 days postpartum, while SSD was at 22.3 ± 7.9 days (P < 0.01); no differences (P > 0.05) in dorsal backfat thickness or average bodyweight between treatments were observed. During the ultrasound-scanning period, four of six cows ovulated in the SSD treatment and five of six in the NSSD. No difference (P > 0.05) was observed at the time of ovulation after progestin implant withdrawal (55.8 ± 7.8 h in NSSD vs 94.5 ± 21.7 h in SSD). The largest follicle diameter at the beginning of the scanning was in SSD treatment (7.25 ± 1.4 mm in SSD vs 5.0 ± 0.8 mm in NSSD), whereas at the time of ovulation, it was similar (15.2 ± 1.8 mm in SSD vs 11.0 ± 1.4 mm in NSSD) between the treatments (P > 0.05). The resumption of ovarian activity was similar between SSD (69 ± 20.7 days, ranging from 42 to 83 days) and NSSD (69.8 ± 6.4 days, ranging from 59 to 73 days). The length of postpartum anoestrus was influenced by the onset of the nadir of body condition score. Energy diet supplementation did not influence the onset of ovarian activity.